PENGEMBANGAN PERMAINAN TEAM SPORTS UNTUK PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA, DAN KESEHATAN SISWA SEKOLAH MENENGAH ATAS - Sudarmono, Martin; Farida, Lulu April; P, Ranu Baskora Aji (Universitas Negeri Semarang, 2015)
Sports game is one of game and sport material that aims to develop learnersâ motor coordination through team play activities. Not all schools teach all the materials in big ball games. Based on the explanation above, it is necessary to develop a great ball game that can develop motor coordination skills of learners. Development procedures used; 1) analyzing the products that will be developed, 2) develop initial product, 3) validation experts, 4) field trial, 5) revision of the product, and the results of product development. Instruments used; 1) the data of pulse capture, (2) the questionnaire related to the learner psychomotor responses, cognitive, and affective (3) observation of the effectiveness of the basic techniques used in the product. Results of this study that have been found; (1) TEAMS SPORT products games, (2) the effectiveness of game products to increase physical activities of students, (3) the TEAMS SPORT game can overcome the limitations of the instructional time allocation, (4) the complexity of motor coordination skill. The conclusion are the use of SPORT TEAMS game product in learning gives the effect to the physical intensity, can cope with limited facilities and infrastructure, can overcome the limitations of instructional time allocation, and provide an experience of complex motor coordination. Suggestions for Sports teachers in high school to use this game at school, in learning a great ball game high school class X.